Microvascular endothelial dysfunction in vascular senescence and disease - Daniel A. Kasal; Daniel A. Kasal; Viviane Sena; Grazielle Vilas Bôas Huguenin; Grazielle Vilas Bôas Huguenin; Andrea De Lorenzo; Eduardo Tibirica (Frontiers in Cardiovascular Medicine)
Cardiovascular disease (CVD) is the main cause of morbidity and mortality in the adult and the elderly, with increasing prevalence worldwide. A growing body of research has focused on the earliest stage of vascular decline—endothelial dysfunction (ED)—which at the microvascular level can anticipate in decades the diagnosis of CVD. This review aims to provide a prospect of the literature regarding the development of ED as an indissociable feature of the aging of the cardiovascular system, highlighting the role of inflammation in the process. Vascular aging consists of a lifelong continuum, which starts with cell respiration and its inherent production of reactive oxygen species. Molecular imbalance is followed by cellular epigenetic changes, which modulate immune cells, such as macrophage and lymphocyte subtypes. These mechanisms are influenced by lifestyle habits, which affect inflammation hotspots in organism, such as visceral fat and gut microbiota. The process can ultimately lead to an environment committed to the loss of the physiological functions of endothelial cells. In addition, we discuss lifestyle changes targeting the connection between age-related inflammation and vascular dysfunction. Addressing microvascular ED represents a critical endeavor in order to prevent or delay vascular aging and associated diseases.